Determinants of productivity of smallholder farmers supplying cassava to starch processors in Nigeria: a baseline evidence - Ojiako, I.A.; Tarawali, G.; Okechukwu, R.U.; Chianu, Jonas N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2017)
The influence of socioeconomic and other household characteristics on the productivity of smallholder farmers supplying cassava to the major commercial starch processors in Nigeria were examined. A multi-stage random sampling technique was used to select 96 farmers working in clusters in selected eight cassava producing states. Data were analyzed using a combination of descriptive and inferential statistics, and multivariate regression techniques. Results revealed the calculated average yield to be 12.39 t/ha thereby leaving an average yield-gap of 7.61 t/ha when compared with an average of 20 t/ha being promoted for farmers under the project. Use of improved varieties (p<0.01) and full-time farming (p<0.05) had significant positive influence on productivity. Also, training, credit use and marital status of farmers influenced productivity positivity at p<0.10 levels. Productivity increased with increase in the variables, but the degree of responsiveness was inelastic in each case. Together the included variables explained 72.1% of the variation in the productivity model. The use of improved cuttings should be accompanied by rigorous but appropriate capacity enhancement programmes to update farmers on modern issues on cassava production and farm management. Empowerment of farmers through linkage to sources of soft loan and other microcredit facilities was recommended, but such efforts should be targeted more on the married and full-time farmers for greater impact.